Cardiac resynchronization therapy in congenital heart disease: Results from the German National Register for Congenital Heart Defects. (15th December 2018) - Flügge, Ann-Katrin; Wasmer, Kristina; Orwat, Stefan; Abdul-Khaliq, Hashim; Helm, Paul C.; Bauer, Ulrike; Baumgartner, Helmut; Diller, Gerhard-Paul; ,
Abstract: Background: Cardiac resynchronization therapy (CRT) is an established option for patients with heart failure. Limited data exists on indications and outcome of CRT in contemporary congenital heart disease (CHD) patients. Methods and results: All patients with CRT registered in the German National Register for Congenital Heart Defects were systematically identified. We analysed data on demographics, type of congenital defect as well as repair, associated conditions, indication for CRT, heart failure medication, combination with a defibrillator or pacemaker and outcome. Overall, 65 patients with CRT were identified. The most common congenital diagnoses were Tetralogy of Fallot (n = 11), congenitally corrected transposition of the great arteries (ccTGA) (n = 9) and double outlet right ventricle (n = 6). The majority of patients (n = 48, 87%) had conventional antibradycardia pacing or ICD indications. Of these, the majority (n = 44) underwent an upgrade to a CRT system to avoid the detrimental consequences of longstanding conventional ventricular single-site pacing, whereas four patients required an ICD due to heart failure and a history of malignant ventricular tachycardia. During a median follow-up of 6.9 years 19 patients developed complications: 16 patients experienced pacemaker lead dysfunction and 3 patients pacemaker infection. Conclusions: The current study based on a large national register for CHD shows that CRT is feasible and can be used as an adjunct in the heart failure treatment of selected CHD patients. Uptake of this therapy proved to be low in this nationwide study and CRT implantation was largely used in patients with a pre-existing pacing indication or those requiring an ICD. Highlights: Heart failure remains a major issue in congenital heart disease (CHD). Reporting results of a nationwide CHD registry on cardiac resynchronisation (CRT). CRT therapy can improve symptoms in selected patients. Uptake of CRT therapy has been slow in our study. Most patients have concomitant anti-bradycardia indications for CRT.